Clinical characteristics and outcomes of oropharyngeal carcinoma related to high‐risk non–human papillomavirus16 viral subtypes. Issue 9 (15th April 2016) - Varier, Indu; Keeley, Brieze R.; Krupar, Rosemarie; Patsias, Alexis; Dong, Joanna; Gupta, Nikita; Parasher, Arjun K.; Genden, Eric M.; Miles, Brett A.; Teng, Marita; Bakst, Richard L.; Gupta, Vishal; et al.
Abstract: Background: The majority of human papillomavirus (HPV)‐related oropharyngeal carcinomas (OPCs) are associated with HPV genotype 16; however, OPC can be associated with other high‐risk non‐HPV16 genotypes. Methods: This was a retrospective analysis of patients with high‐risk non‐HPV16 OPC treated at a single tertiary institution. Sociodemographic and clinical information was obtained by chart review. HPV genotype was determined by polymerase chain reaction (PCR). Baseline data and outcomes were compared between HPV16 and high‐risk non‐HPV16 groups. Results: High‐risk non‐HPV16 genotypes accounted for 9% of HPV‐related OPC. Of the 27 total high‐risk non‐HPV16 OPCs, HPV35 was most prevalent (48%). High‐risk non‐HPV16 OPC presented at a slightly higher age ( p = .021) and higher clinical T classification ( p = .008) compared to HPV16 OPC, but there was no significant survival difference. Conclusion: Clinical characteristics of high‐risk non‐HPV16 OPC were largely consistent with those of HPV16 OPC. Additional multi‐institutional studies will be required to demonstrate conclusively that the favorable prognosis of patients with HPV16 applies to all high‐risk HPV types. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1330–1337, 2016